Paradigms lost: integrating history and organization studies. Issue 4 (1st October 2016) - Decker, Stephanie
Abstract: This article reviews recent attempts at mapping research paradigms in Management and Organizational History and argues that the old distinctions between supplementarist, integrationist, and reorientationist approaches have been superseded by attempts at integrating historical research in organization studies. A typology of these integrationist approaches differentiates between pluralist and unitary integration, as well as between models based on either historical theory or organization theory. Each has distinct weaknesses and strengths, but essentially all limit their integration of historical research paradigms to only a few. As a result, there is a danger that history might become reduced to a methodology, an empirical endeavor, narrative representations, or indeed be considered the subject of research rather than a research approach in its own right. I argue that all of these present an impoverished picture of the rich research traditions available in the discipline of history, which has unique insights and approaches to offer to the study of organizations.